Determination of Water Quality Parameters of Yesilirmak River, Turkey - Yerel, Suheyla; Ankara, Huseyin; Ozbay, Nurgul (Asian Journal of Chemistry, 2010)
In this study, the surface water quality of the Yesilirmak river in Turkey is assessed by using multivariate statistical techniques. These techniques were applied to the water quality parameters obtained from the six different surface water quality monitoring stations. Factor analysis represents that agricultural, domestic waste and organic pollution caused differences in terms of water quality. Hierarchical cluster analysis revealed two different clusters of similarities between the monitoring stations, reflecting different chemical properties and pollution levels in the studied river. These results present that agricultural, domestic waste and organic pollution caused differences in terms of river quality in the north and northwest part of the Yesilirmak river, Turkey. Thus, this paper represents the usefulness of multivariate statistical techniques, including factor analysis and hierarchical cluster analysis, for helping determination makers in hydrochemical studies.